Influence of extraction methods on fatty acid composition, total phenolic content and antioxidant capacity of Citrus seed oils from the Atacama Desert, Chile - Gabino Garrido; Wai-Houng Chou; Carolina Vega; León Goïty; Marisela Valdés (GarVal Editorial Ltda., 2019)
Context: In the north of Chile, the Atacama Desert and the town of Pica are located, where numerous fruits grow, including citrus ecotypes that generate waste such as the seeds of these fruits. Aims: To evaluate the influence of extraction methods on fatty acid composition, nutritional quality indexes of lipids, total phenolic content and antioxidant capacity of acid lime (AL) and sweet orange (SO) seed oils from Pica oasis. Methods: Extraction of these oils was performed using Soxhlet (SE) and direct (D-UAE) or indirect (I-UAE) ultrasound-assisted extraction techniques. Results: The highest oil yields were obtained using SE (AL = 31.90%, SO = 33.32%). These oils were found to be a rich source of unsaturated fatty acids. Linoleic (36.69%, SE), palmitic (21.90%, SE), oleic (18.07%, UAE-D), a-linolenic (11.45%, D-UAE), and myristoleic (5.91%, D-UAE) acids were the highest concentrations found in AL, while in SO they were oleic and a-linolenic acids (22.54 and 4.53%, respectively) in SE. Total phenolic contents were found without statistical differences between extraction methods (AL =0.719 - 0.787 mg GAE/g oil and SO = 0.653 - 0.915 mg GAE/g oil), except D-UAE SO (0.653 mg GAE/g oil). These oils had similar radical scavenging capacity and reducing power, except in ORAC method (41.99 vs. 96.39 µmol TE/g oil for AL and SO, respectively both in SE). The indexes of nutritional quality were similar among the different methods for the same species, but some of them presented statistically significant differences between the species. Conclusions: An influence of extraction methods on fatty acid composition, total phenolic content and antioxidant capacity of AL and SO seed oils with better results achieved using SE followed by I-UAE was demonstrated. This work establishes the potential source of nutritional compounds of these seeds that grow in the Atacama Desert, Chile.